Improving Student’s English Vocabulary Using Duolingo Application - Febriani, Riva; Bunau, Eusabinus; Surmiyati; Gatot Sutapa Yuliana, Yohanes; Salam, Urai (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This research was Classroom Action Research (CAR) which aimed to implement the use of the Duolingo Application to improve students' English vocabulary. It was conducted in two cycles by the researcher. The subject in this research was the students of 12th grade social 3 of SMA Negeri 1 Selakau in Academic Year 2021/2022 which consists of 15 students. The researcher found that the problem of this research was the students could not understand the vocabulary of the verb, then they had difficulty in understanding the English textbook and it was a big problem for the twelfth' grade students face the English examination. The data in this research were collected by using an observation checklist and test. The research showed the use of the Duolingo Application successfully could improve students’ vocabulary of present and past verbs. As observed by the researcher, the improvement was indicated by aspects of students' active and passive in answering the vocabulary questions from the teacher. The results found through the process of using the Duolingo Application, students were likely to raise their hands to answer the translation of twenty list questions of vocabulary from the teacher. Then, the students have a better understanding of the vocabulary’s meaning by a small number of students did not raise their hands, raise their hands, and answered correctly in a quick time. Therefore, this research was successful in improving the students’ vocabulary of the verb by using Duolingo Application.